The Implementation of the International Health Regulations on Vector-Borne Diseases: A Scoping Review of the Qualitative Evidence Performed Worldwide - Ana Margarida Alho; Carlos Quelhas; Inês Subtil; Tiago Adrego; José Durão (Karger Publishers, 2023)
Introduction: The International Health Regulations were created by the World Health Organization with the purpose of preventing the international spread of diseases. The 196 signatory countries are bound by this international agreement. In this article, we conducted a scoping review of the literature concerning the implementation and operationalization of measures at both the continental and national levels to prevent the spread of vector-borne diseases. The purpose was to understand the main strategies and policies adopted, as well as how they have been operating. Methods: Out of an initial search on PubMed™, SCOPUS™, and Web of Science™ using combinations of "International Health Regulations" and "vector-borne diseases", 75 references were obtained, of which 27 were included after careful qualitative analysis. Results: Publication dates of included articles ranged from 1996 to 2022. Four major categories of measures were identified: (a) surveillance and epidemic intelligence; (b) Declaration of Public Health Emergency of International Concern; (c) measures in Points of Entry; and (d) vaccination status. Implemented measures were found in all continents: Africa, Oceania (Australia), Asia (China, India, Taiwan), Europe (Ireland, the Netherlands, and Mediterranean countries), North America (USA), and South America (Brazil). Yellow fever, Zika, Dengue, and Chikungunya were the most cited vector-borne diseases but Crimean-Congo hemorrhagic fever, Japanese encephalitis, Lyme disease, Malaria, Leishmaniasis, Tick-borne encephalitis, and West Nile fever were also mentioned. Conclusion: There are severe asymmetries across countries on the implementation of international regulations with regards to vector-borne diseases, particularly on the issue of surveillance systems. State Parties should consider the lessons learned from the pandemic and perfect their core capacities to prevent future outbreaks of infectious diseases.